A corpus-based frequency list of Arabic sight words for grades 4–6 - Ahmad Oweini,; Noura El-Far, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study updates and extends the foundational work of Oweini and Hazoury (2010) by developing a new corpus-based list of Arabic sight words for grades 4-6 in Lebanese private schools. It addresses the lack of recent, systematic descriptions of high-frequency Arabic words and examines their role in reading fluency and comprehension. Fifteen commonly used Arabic reading textbooks were analyzed, and words were categorized by type and morphological structure. The findings confirm the dominance of functional words and reflect the influence of diglossia and Arabic orthographic complexity on sight word identification. Comparison with existing word lists and frequency dictionaries shows strong overlap but also highlights areas requiring revision. This updated frequency list offers educators and textbook designers linguistically grounded evidence for improving reading materials. The study also recommends expanding future research using digital corpus tools to support larger-scale frequency analyses.